Implementasi Python API dengan Framework Flask sebagai Cloud Run Service Untuk Proses Update di PT. XYZ - Rizky Nandang Pratama; Yeremia Alfa Susetyo (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This study focuses on implementing an API using the Flask framework in the Python programming language, which is then deployed as a Cloud Run service to facilitate data updating processes in XYZ company. By utilizing Flask as a lightweight and user-friendly API development framework, we successfully integrated it into the Google Cloud Platform's (GCP) Cloud Run environment to leverage its scalability and high performance. Our testing indicates that the Cloud Run service provides benefits in terms of automatic scalability, easy infrastructure management, and high reliability in efficiently processing data updates. Thus, the findings of this research affirm that this approach offers an effective solution for enhancing data updating processes in XYZ company, leveraging the advantages of Flask technology and the Cloud Run service.